2021
DOI: 10.1007/s10965-021-02414-3
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of hemp fibres for use in rotational moulding

Abstract: The benefit of using alkali-treated hemp fibre as the reinforcement for rotationally moulded polyethylene composites was evaluated in this research. Untreated and alkali-treated hemp fibre were characterised using different techniques such as scanning electron microscopy (SEM), thermal analysis, and Fourier transform infrared spectroscopy (FT-IR). These techniques showed that the alkali treatment removed non-cellulosic components from hemp fibres, which improved their separation and thermal resistance. Composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…The composites with treated Ricinus also led to thicker walls due to the formation of clusters and voids appearing. In any case, the inner surface of the parts shows an acceptable quality, with no excessive number of voids or fiber balls inside the mold (not integrated into the part), as pointed out in other papers [33]. Darker color and intense smell are obtained for untreated material parts, which means that NaOH treatment is needed in this case to increase the thermal stability (as also observed from TGA analysis).…”
Section: Composites Productionsupporting
confidence: 57%
See 1 more Smart Citation
“…The composites with treated Ricinus also led to thicker walls due to the formation of clusters and voids appearing. In any case, the inner surface of the parts shows an acceptable quality, with no excessive number of voids or fiber balls inside the mold (not integrated into the part), as pointed out in other papers [33]. Darker color and intense smell are obtained for untreated material parts, which means that NaOH treatment is needed in this case to increase the thermal stability (as also observed from TGA analysis).…”
Section: Composites Productionsupporting
confidence: 57%
“…The literature shows that the introduction of fillers significantly affects tensile and impact strength while modules remain unchanged or even tend to increase [12,42]. For example, Oliveira et al have found that using 5% hemp fibers resulted in a reduction in tensile strength and modulus higher than 50%; the use of NaOH-treated fibers allows for reducing this drop, especially for modulus [33]. Abhilash and collaborators finally found that 10% of bamboo fibers can be introduced into the PE matrix without significant decreases in mechanical properties (apart from impact strength, which is also significantly decreased) [19].…”
Section: Mechanical Properties Of the Compositementioning
confidence: 99%
“…Sari and collaborators [ 40 ] also proposed the use of the plasma activation of PE to increase its adhesion with coir fibers, demonstrating improvements in impact strength—although only 5% fiber composites were produced. Finally, Oliveira et al [ 41 ] were only able to introduce up to 5% of hemp fibers into a PE matrix without worsening the mechanical properties, even for NaOH- and MAPE-treated fibers.…”
Section: Discussionmentioning
confidence: 99%
“…The infrared analysis confirms the chemical composition data obtained by hydrolysis, which show a lower lignin content for the leaves and roots samples, and a higher proportion of cellulose for the fibres. As shown in Figure 7 , at 1730 cm −1 the peak corresponding to the C=O vibration of ketone or carbonyl groups (mainly associated with the presence of hemicellulose [ 32 ], although it may also be due to pectins and waxes) can be observed. This peak occurs for all parts of the plant, although for leaf and root samples, this peak is of very low intensity.…”
Section: Resultsmentioning
confidence: 99%